Strategies to Improve Paraphrasing Skills for Students in Compiling Final Assignments - Sudirman, Wahyu Febri Ramadhan; Priyatno, Arif Mudi; Rizqi, Eka Roshifita; Rizki, Syafnur Muhammad (Global Sustainability Research Institute, 2025)
Paraphrasing ability is an essential skill that students must have to improve the quality of academic writing and avoid plagiarism. However, many students still struggle to rephrase information effectively due to limited vocabulary, understanding of language structure, and lack of practice in academic writing. Therefore, this community service activity aims to improve the paraphrasing skills of Patompo University students through online training based on Zoom Meetings. The training method applied includes five main stages, namely (1) presentation of material on paraphrasing techniques and academic ethics, (2) discussion and question and answer sessions to clarify participants' understanding, (3) direct practice in rephrasing academic texts, (4) mentoring and feedback on students' paraphrasing results, and (5) assessment of academic manuscripts as a final evaluation. This program also integrates supporting technology to help students evaluate the quality of their paraphrases. The results of this activity show an increase in students' understanding of paraphrasing techniques and their ability to apply them in academic work. With this training, it is hoped that students can be more confident in writing originally, improve critical thinking skills, and build a more ethical and professional academic culture.